Air Pollution Impact on Pregnancy Outcomes in Como, Italy. Issue 1 (January 2016) - Capobussi, Matteo; Tettamanti, Roberto; Marcolin, Luca; Piovesan, Luca; Bronzin, Silvia; Gattoni, Maria Elena; Polloni, Ilaria; Sabatino, Giuliana; Tersalvi, Carlo A.; Auxilia, Francesco; Castaldi, Silvana
Abstract : Objective: This retrospective observational study investigates the association between maternal exposure to air pollutants and pregnancy adverse outcomes in low urbanization areas. Methods: We used multivariate regression analysis to estimate, in the Como province (2005–2012), the effects of NOx, NO2, SO2, O3, CO, and PM10 on low birth weight (LBW), babies small for gestational age (SGA), and preterm birth (PTB). Results: PTB was inversely associated with high (5.5 μg/m 3 ) exposure to SO2 (adjusted odds ratio [aOR] = 0.74, 95% confidence interval [95% CI] = 0.58–0.95) and to CO (1.8 mg/m 3, aOR = 0.84, CI = 0.72–0.99). PTB risk increased with second trimester exposure to NOx (118.3 μg/m 3, aOR = 1.53, CI = 1.25–1.87), while LBW risk increased with third trimester PM10 (56.1 μg/m 3, aOR = 1.44, CI = 1.03–2.02). SGA was inversely associated with third trimester NOx (115.8 μg/m 3, aOR = 0.89, CI = 0.79–0.99). Conclusions: Exposure to SO2 and CO seems to postpone delivery: a longer gestation could compensate for maternal hypoxemic-hypoxic damage.